Analysis of Potential in Asymmetric Braking for Autonomous Applications - Volz, Patrick (My University, 2018)
Striving for automated commercial vehicles, the execution of steering commands has to be highly reliable in order to guarantee the manoeuvrability in any driving situation: In the event of the primary steering actuator’s failure, highly and fully automated vehicles have to provide their own fall-back performance since the human driver is relieved of any driving responsibility. Consequently, an additional, independent fall-back level for this steering actuator is essential, which undertakes the steering task and guarantees the driving safety. Although it is possible to establish the required levels of redundancy by implementing similar, additional steering actuators, this design would significantly increase the cost and the box volume of the system. On that account, this thesis project investigates the manoeuvrability of overactuated commercial vehicles using the mounted wheel brakes in detail. This approach uses the existing actuators of the respective vehicle configuration, limiting the system costs and the development effort. The first part of the project aims at the development of a reconfigurable motion control system which generates the desired vehicle motion to perform a defined driving manoeuvre while ensuring driving safety. Accordingly, this system covers all the steps from the computation of directional and velocity related commands, the control of the involved vehicle motions, to the coordination and control of the accessible brake actuators. This results in an asymmetric brake torque distribution. In order to structure the system functionalities and to enable the reusability of the controller for various vehicle configurations, the architecture of the control design needs to be modular. For the verification of the control unit’s development, the project scope comprises the analysis of the system performance in predefined driving manoeuvres. Therefore, several demanding manoeuvres are carried out on the test track and in the simulation environment. Based on the simulation and vehicle testing results, the vehicle’s steerability as well as the driving precision and stability are evaluated. Finally, the system’s performance is compared to the primary steering actuator intended for the driving task, since it sets the benchmark for the manoeuvrability. In direct comparison of the steering characteristics, the asymmetric braking technology is able to keep up with the intended steering actuator. Despite the lower steering dynamics, the motion control system ensures a stable motion in all the manoeuvres. In conclusion, the asymmetric braking has the potential of providing the required fall-back level and ensure the execution of the steering commands.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering